Effect of laser parameters on the surface cleaning of galvanised steel by laser engraving process - Abu Bakar, Mohd Hadzley; Ab Wahab, Norfariza; Azhar, Anis Afuza; Adam, Abdul Aziz; Herawan, Safarudin Gazali; Thongkaew, Kunlapat; Fairuz, M. R. (Universiti Malaysia Perlis, 2021)
Laser cleaning is a method of removing layers of material from a surface by using laser irradiation. The energy from the laser provides a textured pattern on the melting surface, as well as colour changes and variations in surface roughness. This study looks into the effect of laser parameters on the cleaning surface of galvanized steel. In particular, the laser engraving method was used to irradiate the selected area by varying the laser power and irradiation cycle. The results show that the upper layer of galvanized steel can be rapidly removed, altering the surface profile and roughness. Increasing laser power and cycling the resultant colour change from white or bright to dark. In terms of surface roughness, the first irradiation cycle demonstrated increasing surface roughness as laser power was increased. The fourth cycle, on the other hand, showed a decrease in surface roughness as the laser power increased. In terms of surface finish, laser engraving at 16W power is recommended due to its best surface roughness of 1.17 μm. In terms of surface profile, laser engrave is suggested to be applied during the fourth irradiation cycle because the surface pattern demonstrated dark appearances and minimal surface roughness.